A deep ultraviolet LED with high carrier recombination and high light output and a preparation method thereof
Patent Information
- Application Number
- CN202310535410.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-05-12
AI Technical Summary
目前大多数紫外LED采用的是p型GaN作为欧姆接触层,但是GaN的禁带宽度较窄,在紫外区域,p型GaN的吸收系数较高,从量子阱中出射的绝大部分紫外光被吸收,不仅大幅降低紫外LED光提取效率,而且还会进一步引起芯片发热,影响芯片寿命;另一方面,有源区的多量子阱结构中存在着较大的自发极化效应和因晶格失配引起的压电极化导致的极化电场,且垒中与阱中的极化电场方向相反,造成量子阱能带发生弯曲倾斜,进而造成量子限制斯塔克效应,使得量子阱内有效带隙减小,电子与空穴的波函数分离,有源区载流子辐射复合效率进一步降低
其中,所述MQW有源区发光层包含多个周期结构,单个周期结构由依次层叠的第一子量子垒层、量子阱层和第二子量子垒层组成,第一子量子垒层为Al组分逐渐增大的AlInGaN层,第二子量子垒层为Al组分逐渐减小的AlInGaN层,所述量子阱层为i型AlInGaN层,所述第一子量子垒层、量子阱层和所述第二子量子垒层之间构成类nip结。
Smart Images

Figure CN116487492B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor optoelectronics, and more particularly to a deep ultraviolet LED with high carrier recombination and high light output, and its preparation method. Background Technology
[0002] Compared to traditional LEDs, deep ultraviolet (DUV) LEDs have lower luminous efficiency, especially when the emission wavelength is less than 280 nm, where the external quantum efficiency of the device is almost no more than 10%. Currently, most UV LEDs use p-type GaN as the ohmic contact layer. However, GaN has a narrow bandgap, and in the ultraviolet region, p-type GaN has a high absorption coefficient. Most of the ultraviolet light emitted from the quantum well is absorbed, significantly reducing the light extraction efficiency of the UV LED and further causing chip heating, affecting chip lifespan. On the other hand, the multi-quantum-well structure in the active region exhibits significant spontaneous polarization effects and piezoelectric polarization caused by lattice mismatch, resulting in a polarization electric field. Furthermore, the polarization electric field in the barrier is opposite in direction to that in the well, causing the quantum well bandgap to bend and tilt, leading to the quantum confinement Stark effect. This reduces the effective bandgap within the quantum well, causing wavefunction separation of electrons and holes, and further reducing the radiative recombination efficiency of carriers in the active region. These problems significantly reduce the luminous efficiency of deep ultraviolet LEDs. Summary of the Invention
[0003] To address the technical problems existing in the prior art, the primary objective of this invention is to provide a high-carrier recombination, high-emission deep ultraviolet LED and its fabrication method. This LED structure comprises an electron injection layer, an MQW (Multi-Quantum Wavelet) active region light-emitting layer, an electron blocking layer, a hole injection layer, and a composite transparent conductive layer. Specifically, the single-period structure of the MQW active region light-emitting layer consists of a first sub-quantum barrier layer, a quantum well layer, and a second sub-quantum barrier layer stacked sequentially. The first sub-quantum barrier layer is an AlInGaN layer with gradually increasing Al content, and the second sub-quantum barrier layer is an AlInGaN layer with gradually decreasing Al content. The AlInGaN layer is an i-type AlInGaN layer, and the quantum well layer is an i-type AlInGaN layer. The first sub-quantum barrier layer, the quantum well layer, and the second sub-quantum barrier layer form a nip-like junction. The composite transparent conductive layer is composed of a wide-bandgap semiconductor superlattice ohmic contact layer, a metal oxide work function adjustment layer, and a wide-bandgap transparent electrode layer stacked sequentially. This effectively improves the overlap rate of electron and hole wave functions, increases the internal quantum efficiency of the device, improves current diffusion and transport characteristics, reduces current crowding effect, enhances the light extraction performance of the device, and improves the luminous efficiency and photoelectric conversion efficiency of deep ultraviolet LEDs.
[0004] This invention provides at least the following technical solutions: A high-carrier recombination high-emission deep ultraviolet LED includes a substrate and an epitaxial stack on the substrate. Along the epitaxial growth direction, the epitaxial stack includes a buffer layer, an electron injection layer, an MQW active region light-emitting layer, an electron blocking layer, a hole injection layer, and a composite transparent conductive layer. An n-type electrode is disposed on the electron injection layer, and a p-type electrode is disposed on the composite transparent conductive layer. The active region light-emitting layer of the MQW contains multiple periodic structures. Each periodic structure consists of a first sub-quantum barrier layer, a quantum well layer, and a second sub-quantum barrier layer stacked sequentially. The first sub-quantum barrier layer is an AlInGaN layer with gradually increasing Al content, and the second sub-quantum barrier layer is an AlInGaN layer with gradually decreasing Al content. The quantum well layer is an i-type AlInGaN layer. The first sub-quantum barrier layer, the quantum well layer, and the second sub-quantum barrier layer form a nip-like junction. The composite transparent conductive layer comprises a wide-bandgap semiconductor superlattice ohmic contact layer, a metal oxide work function adjustment layer, and a wide-bandgap transparent electrode layer, which are stacked sequentially.
[0005] Furthermore, the first sub-quantum barrier layer gradually increases in Al composition. The second sub-quantum barrier layer is composed of layers, with the Al composition gradually decreasing. The structure consists of layers, where x1 increases from 0.48 to 0.62, x2 decreases from 0.62 to 0.48, 0.13 < y1 < 0.24, and 0.13 < y2 < 0.24. The thickness of the first sub-quantum barrier layer and the second sub-quantum barrier layer is 2.5~5nm. The quantum well layer is selected The quantum well layer has a thickness of 2-4 nm, where 0.41 < a < 0.53 and 0.13 < b < 0.21.
[0006] Furthermore, quantum wells In the layer, Al component a is selected as 0.44, and In component b is selected as 0.15.
[0007] Furthermore, the band gap of the wide bandgap semiconductor superlattice structure is larger than that of p-type GaN.
[0008] Furthermore, the wide-bandgap superlattice ohmic contact layer is made of Mg-doped material. Superlattice structure or Mg doping Superlattice structure, in which, and For the trap layer, and For the layer, a1≠a2, 0.4<a1<0.5, 0.4<a2<0.5, b1≠b2, 0.22<b1<0.29, 0.22<b2<0.29, c1≠c2, 0.35<c1<0.45, 0.65<c2<0.75.
[0009] Furthermore, the metal oxide work function adjustment layer is selected from ITO, FTO, IZO or Ga-doped ZnO.
[0010] Furthermore, the wide-bandgap transparent electrode layer is selected from graphene or GaO layers, and its thickness is selected from 1 to 4 layers.
[0011] Furthermore, the number of cycles of the wide-bandgap semiconductor superlattice ohmic contact layer is selected as 3 to 10, and in a single cycle, the thickness of the well layer is 1 nm and the thickness of the barrier layer is 1 nm.
[0012] Furthermore, the electron injection layer is selected as an n-type AlGaN layer, and the electron blocking layer is selected as a p-type AlGaN layer.
[0013] This invention also provides a method for fabricating a deep ultraviolet LED with high carrier recombination and high light output, comprising the following steps: An epitaxial stack consisting of a buffer layer, an electron injection layer, an MQW active region light-emitting layer, an electron blocking layer, a hole injection layer, and a wide bandgap semiconductor superlattice ohmic contact layer is sequentially grown on the substrate. The epitaxial stack is etched to a certain depth in the electron injection layer to form an n-type platform; A metal oxide work function adjustment layer and a wide bandgap transparent electrode layer are sequentially formed on the wide bandgap semiconductor superlattice ohmic contact layer, and the wide bandgap semiconductor superlattice ohmic contact layer, the metal oxide work function adjustment layer and the wide bandgap transparent electrode layer constitute a composite transparent conductive layer. A p-type electrode is formed on the wide-bandgap transparent electrode layer, and an n-type electrode is formed on the platform; The MQW active region light-emitting layer comprises multiple periodic structures. Each periodic structure consists of a first sub-quantum barrier layer, a quantum well layer, and a second sub-quantum barrier layer stacked sequentially. The first sub-quantum barrier layer is an AlInGaN layer with gradually increasing Al content, and the second sub-quantum barrier layer is an AlInGaN layer with gradually decreasing Al content. The quantum well layer is an i-type AlInGaN layer. The first sub-quantum barrier layer, the quantum well layer, and the second sub-quantum barrier layer form a nip-like junction.
[0014] This invention optimizes the active region of the quantum well by employing AlInGaN with reverse and forward gradients of Al composition introduced into the quantum barrier. The forward gradient of Al composition generates a three-dimensional electron gas, forming the n-region, while the reverse gradient of Al composition generates a three-dimensional hole gas, forming the p-region. An intrinsic quantum well region is positioned between the p-region and the n-region, forming a nip-like junction structure. In this nip-like junction structure, the electric field caused by the three-dimensional electron gas and the three-dimensional hole gas is opposite in direction to the original polarization electric field. While avoiding the introduction of doping impurities, this effectively reduces the polarization electric field in the active region, reduces band bending, and increases the overlap rate of electron and hole wave functions, thereby improving the radiative recombination efficiency of charge carriers and the luminous efficiency of deep ultraviolet LEDs. On the other hand, a composite transparent conductive layer is constructed by using a wide-bandgap semiconductor superlattice ohmic contact layer, a metal oxide work function adjustment layer, and a wide-bandgap transparent electrode layer. The introduction of the wide-bandgap semiconductor superlattice ohmic contact layer replaces the traditional p-type GaN contact layer. By adjusting the bandgap, a larger bandgap is formed, resulting in a smaller absorption coefficient and reducing the absorption of ultraviolet light by the contact layer. At the same time, it can improve the ionization rate of Mg acceptors and the in-band tunneling electric field, thereby increasing the hole concentration obtained by the LED. The wide-bandgap transparent electrode layer has high conductivity and light extraction performance. The metal oxide work function adjustment layer is set between the wide-bandgap semiconductor superlattice ohmic contact layer and the wide-bandgap transparent electrode layer. This effectively reduces the potential barrier and contact resistance, reduces the overall current transmission resistance, alleviates current congestion, and improves the transmittance of the device in the visible light range, thereby improving the light extraction performance of the device and the luminous efficiency and photoelectric conversion efficiency of the deep ultraviolet LED. Attached Figure Description
[0015] Figure 1 This is a schematic diagram of the structure of a deep ultraviolet LED according to an embodiment of the present invention.
[0016] Figure 2 This is a graph showing the relationship between the band gap and lattice constant of group III nitrides.
[0017] Figure 3 This is a schematic diagram illustrating the compositional changes of the quantum barrier and quantum well in the light-emitting layer of the multi-quantum-well active region according to an embodiment of the present invention.
[0018] Figure 4 This is a schematic diagram of the three-dimensional electron / hole gas distribution and electric field direction within the active region of a multi-quantum well according to an embodiment of the present invention.
[0019] Figure 5 This is a schematic diagram illustrating the compositional changes of the quantum barrier and quantum well in the multi-quantum-well active region light-emitting layer of the present invention, which is a comparative example.
[0020] Figure 6 This is a schematic diagram of the three-dimensional electron / hole gas distribution and electric field direction in the multi-quantum well active region of the present invention. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will now be clearly and completely described with reference to the accompanying drawings. The described embodiments are merely some, not all, of the embodiments of the present invention. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0022] The use of terms such as "first" and "second" to describe various elements, layers, regions, and sections in this specification is not intended to be limiting. The use of terms such as "having," "containing," "including," and "comprising" are open-ended terms, indicating the presence of the stated elements or features, but not excluding additional elements or features, unless the context clearly indicates otherwise.
[0023] One embodiment of the present invention provides a deep ultraviolet LED with high carrier recombination and high light output, such as... Figure 1 The diagram shows a substrate 1 and an epitaxial stack on the substrate 1. The epitaxial stack includes a buffer layer 2, an electron injection layer 3, an MQW active region light-emitting layer 4, an electron blocking layer 5, a hole injection layer 6, and a wide-bandgap semiconductor superlattice ohmic contact layer 7. The epitaxial stack includes a mesa that exposes a portion of the electron injection layer, and an n-type electrode 11 is disposed on the mesa. A metal-oxide work function adjustment layer 8 is disposed on the wide-bandgap semiconductor superlattice ohmic contact layer 7, and a wide-bandgap transparent electrode layer 9 is disposed on the metal-oxide work function adjustment layer 8. The wide-bandgap semiconductor superlattice ohmic contact layer 7, the metal-oxide work function adjustment layer 8, and the wide-bandgap transparent electrode layer 9 constitute a composite transparent conductive layer. A p-type electrode 10 is disposed on the wide-bandgap transparent electrode layer.
[0024] In one embodiment, the buffer layer 2 is an AlN buffer layer, and the electron injection layer 3 is an n-type AlGaN electron injection layer, preferably with a thickness of 4 μm, an Al composition content of preferably 0.6%, and a doping concentration of 1 × 10⁻⁶. 18 ~1×10 19 cm -3 The growth temperature is 800~1200℃, and the doping type is Si doping.
[0025] The MQW active region light-emitting layer 4 is composed of periodically arranged quantum well layers and quantum barrier layers stacked together, with a period number ranging from 3 to 10. The quantum barrier layer includes a first sub-quantum barrier layer and a second sub-quantum barrier layer. The first sub-quantum barrier layer is composed of Al with gradually increasing Al content. x1 In y1 Ga 1-x1-y1 In layer N, x1 increases from 0.48 to 0.62, 0.13 < y1 < 0.24, and the second sub-quantum barrier layer is composed of Al with gradually decreasing Al content. x2In y2 Ga 1-x2-y2 In the N-layer, x2 decreases from 0.62 to 0.48, 0.13 < y1 < 0.24, and the quantum well layer is type i Al. a In b Ga 1-a-b In layer N, 0.41 < a < 0.53, 0.13 < b < 0.21. Among these, the Al components x1 and x2 in the quantum barrier layer are greater than the Al component a in the quantum well layer; the selection of Al and In components in the quantum well and quantum barrier layers is based on... Figure 2 The relationship between the band gap and lattice constant of group III nitrides is shown.
[0026] In a single cycle, the thickness of the first and second sub-quantum barrier layers is equal, both ranging from 2.5 to 5 nm, while the thickness of the quantum well layer is 2 to 4 nm. In a preferred embodiment, the thickness of both the first and second sub-quantum barrier layers is 5 nm, and the thickness of the quantum well layer is 3 nm. A three-dimensional electron / hole gas is generated by using AlInGaN with forward and reverse Al composition gradients on the quantum barrier in the active region of the quantum well. The first and second quantum barrier layers, together with the quantum well region located between them, constitute a nip-like junction structure. This reduces the polarization electric field in the active region, decreases band bending, and improves the overlap rate of the electron and hole wave functions while avoiding the introduction of doping impurities.
[0027] The quantum well layer and its adjacent sub-quantum barrier layers form a nip junction structure. In a preferred embodiment, the ultraviolet band is controlled at 265 nm by quaternary alloy lattice matching. In the quantum well layer, the Al composition is 0.44 and the In composition is 0.15, with a band gap of 3.86 eV and a lattice constant of 0.321 nm. In the quantum barrier, the Al composition first gradually changes from 0.62 to 0.48 in the reverse direction and then from 0.48 to 0.62 in the forward direction, with the reverse and forward changes occurring at the same time and rate. The In composition is 0.13 to 0.24. By adjusting these parameters, the lattice constant of the quantum barrier layer is made close to that of the quantum well layer, and the band gap of the quantum barrier is greater than that of the quantum well layer. For example, on the quantum barrier layer, when the Al composition is 0.62 and the In composition is 0.16, the band gap at that point on the quantum barrier layer is 4.32 eV, which is greater than the band gap of the quantum well (3.86 eV). Its lattice constant is 0.320 nm, and the lattice mismatch with the quantum well layer is only 0.001. When the Al composition on the quantum barrier layer is 0.48 and the In composition is 0.13, the band gap at that point on the quantum barrier layer is 4.05 eV, which is greater than the band gap of the quantum well (3.86 eV). Its lattice constant is 0.320 nm, and the lattice mismatch with the quantum well layer is also only 0.001.
[0028] In one embodiment, such as Figure 3 and Figure 4 As shown, the first sub-quantum barrier layer, the i-type AlInGaN well layer, and the second sub-quantum barrier layer are stacked in sequence to form a single MQW cycle of a nip-like structure. Figure 4 A schematic diagram of the three-dimensional electron / hole gas distribution and electric field direction within the emitting layer of a multi-quantum-well active region is shown in an embodiment. Due to the compositionally graded AlInGaN quantum barrier layer, a polarization gradient exists, leading to an imbalance of polarization charges, which in turn induces the generation of 3DEG and 3DHG. The original polarization electric field direction is as follows: Figure 4 As shown by the solid arrows, to maintain the electrical neutrality of AlInGaN, 3DEG and 3DHG are induced in the AlInGaN barrier layers with forward and reverse gradients in Al composition, respectively. The region with forward gradient (i.e., gradually increasing) Al composition on the next quantum barrier forms an n-type region, and the region with reverse gradient (i.e., gradually decreasing) Al composition on the next quantum barrier forms a p-type region. The quantum well region between these two is the intrinsic region (i-region), constituting a nip-like junction structure. The direction of the induced electric field is as follows: Figure 4 As shown by the dashed arrow, the polarization field is opposite to the original polarization field, thus reducing the polarization field in the active region. By selecting the In composition, the lattice mismatch between the quantum well and the quantum barrier can be reduced, further suppressing the quantum confinement Stark effect. The nip-like junction structure formed through bandgap modulation avoids the introduction of dopant impurities and effectively reduces the polarization field in the active region, decreasing band bending and increasing the overlap rate of electron and hole wave functions. This effectively increases the internal quantum efficiency and improves the luminous efficiency of deep ultraviolet LEDs.
[0029] In this embodiment, a nip-like junction structure is introduced to optimize the active region of the quantum well, thereby reducing the overall polarization electric field and increasing the overlap rate of electron and hole wave functions. Simultaneously, a composite transparent conductive layer structure is introduced to optimize the ohmic contact layer and the light-emitting layer, improving current diffusion and transmission characteristics, reducing current crowding effects, and also reducing the absorption of ultraviolet light by the contact layer. This significantly improves the light extraction performance of the device, thereby enhancing the luminous efficiency and photoelectric conversion efficiency of the deep ultraviolet LED.
[0030] In a pair of proportions, such as Figure 5 and Figure 6 As shown, the second sub-quantum barrier layer, the i-type AlInGaN well layer, and the first sub-quantum barrier layer are stacked sequentially to form a single MQW cycle of a nip-like structure. The arrangement of other layers in this comparative example is the same as... Figure 1 The embodiment shown is the same. The thickness of the first sub-quantum barrier layer and the second sub-quantum barrier layer are equal, both of which are 5 nm thick, and the thickness of the quantum well is 3 nm. Figure 5This diagram illustrates the compositional changes in the quantum barrier and quantum wells within the light-emitting layer of the multi-quantum-well active region in this comparative example. In the quantum barrier layer, the Al composition first gradually changes from 0.48 to 0.62 in the forward direction and then from 0.62 to 0.48 in the reverse direction, with the same time and rate for both the forward and reverse changes. By adjusting and selecting the In composition, the lattice constant of the quantum barrier is made close to that of the quantum well, and the band gap of the quantum barrier is larger than that of the quantum well. The In composition is selected from 0.13 to 0.24. In the quantum well layer, the Al composition is consistently 0.44, and the In composition is consistently 0.15, with a band gap of 3.86 eV and a lattice constant of 0.321 nm.
[0031] Figure 6 This diagram illustrates the three-dimensional electron / hole gas distribution and electric field direction within the multi-quantum-well active region of this comparative example. The original polarization electric field direction is shown below. Figure 6 As shown by the solid arrows, a reverse gradient of the Al component on the quantum barrier induces a 3DHG, forming the p-region. On the next quantum barrier, a forward gradient of the Al component induces a 3DEG, forming the n-region. The quantum well region between these two forms the intrinsic region (i-region), constituting a nip-like junction structure. The direction of the induced electric field generated is as follows: Figure 6 As indicated by the dashed arrow, the direction is the same as the original polarization electric field. Since there is no component gradient in the quantum well, this induced electric field does not weaken the polarization in the quantum well. However, since there is an Al component gradient in the quantum barrier, this induced electric field can reduce the polarization on the quantum barrier layer. Compared with the above embodiment, this comparative example is less effective in improving the radiative recombination efficiency of charge carriers in the active region.
[0032] An electron blocking layer 5 is disposed on the active region light-emitting layer 4 of the MQW to suppress electron leakage. The electron blocking layer 5 is an AlGaN electron blocking layer. In a preferred embodiment, the electron blocking layer 5 is an AlGaN electron blocking layer with a thickness of 10 nm. 0.85 Ga 0.15 The electron blocking layer has an electron density of 700℃ to 1100℃.
[0033] Hole injection layer 6 is a p-type AlGaN hole injection layer, disposed on electron blocking layer 5, with a doping concentration of 1×10⁻⁶. 18 ~1×10 19 cm -3 In a preferred embodiment, an Al layer with a thickness of 50 nm is selected. 0.4 Ga 0.6 The N-hole injection layer has Mg as its p-type dopant at a concentration of 1×10⁻⁶. 18 cm -3 Its growth thickness is 50nm.
[0034] A composite transparent conductive layer is disposed on the hole injection layer. The composite transparent conductive layer consists of a wide-bandgap semiconductor superlattice ohmic contact layer 7, a metal oxide work function adjustment layer 8, and a wide-bandgap transparent electrode layer 9. The wide-bandgap semiconductor superlattice ohmic contact layer 7 is disposed on the hole injection layer 6 and is made of Mg-doped metal oxide. Superlattice structure or Mg doping The superlattice structure has a period number of 3 to 10, where a1 ≠ a2, a1 < a2, 0.4 < a1 < 0.5, 0.4 < a2 < 0.5, b1 ≠ b2, b1 < b2, 0.22 < b1 < 0.29, 0.22 < b2 < 0.29, c1 ≠ c2, c1 < c2, 0.35 < c1 < 0.45, 0.65 < c2 < 0.75.
[0035] In a preferred embodiment, Al is selected. 0.42 In 0.24 Ga 0.34 N / Al 0.45 In 0.26 Ga 0.29 N superlattice ohmic contact layer, in which Al 0.42 In 0.24 Ga 0.34 The N layer is a well layer, Al 0.45 In 0.26 Ga 0.29 The N-layer is a barrier layer with 10 periods. Within a single superlattice period, both the well and barrier thicknesses are 1 nm. This quaternary superlattice structure, acting as an ohmic contact layer, replaces the traditional p-type GaN contact layer. Through a larger bandgap, it achieves a smaller absorption coefficient, significantly reducing ultraviolet light absorption by the contact layer. This further enhances the ionization rate of the Mg acceptor and the in-band tunneling electric field, thereby increasing the hole concentration obtained by the device.
[0036] The metal oxide work function adjustment layer 8 is made of ITO, FTO, IZO, or Ga-doped ZnO; in a preferred embodiment, Ga-doped ZnO is used, which further improves the conductivity of ZnO, and its thickness is 300 nm. The wide bandgap transparent electrode layer 9 has a thickness of 1 to 4 layers and is made of graphene or GaO; in a preferred embodiment, a single layer of graphene is used, which is transferred onto the metal oxide work function adjustment layer 8. Using graphene, which has high light transmittance, as the conductive electrode layer can greatly improve the transmittance in the visible light range. At the same time, the metal oxide work function adjustment layer 8 is inserted between the graphene layer and the superlattice ohmic contact layer 7 to further reduce the potential barrier and contact resistance, and alleviate current congestion.
[0037] In a preferred embodiment, the p-type electrode 10 is a Ni / Au electrode with a Ni layer thickness of 20 nm and an Au layer thickness of 50 nm. The n-type electrode 11 is a Ni / Au electrode with a Ni layer thickness of 20 nm and an Au layer thickness of 50 nm.
[0038] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A high-carrier recombination, high-emission deep ultraviolet LED, comprising a substrate and an epitaxial stack on the substrate, wherein, along the epitaxial growth direction, the epitaxial stack comprises a buffer layer, an electron injection layer, an MQW (Multi-mode Light-Emitting) active region light-emitting layer, an electron blocking layer, a hole injection layer, and a composite transparent conductive layer, wherein an n-type electrode is disposed on the electron injection layer, and a p-type electrode is disposed on the composite transparent conductive layer; characterized in that, The active region light-emitting layer of the MQW comprises multiple periodic structures. Each periodic structure consists of a first sub-quantum barrier layer, a quantum well layer, and a second sub-quantum barrier layer stacked sequentially. The first sub-quantum barrier layer has an Al composition that gradually increases. The second sub-quantum barrier layer has a gradually decreasing Al composition. The quantum well layer has the following characteristics: x1 increases from 0.48 to 0.62, x2 decreases from 0.62 to 0.48, 0.13 < y1 < 0.24, and 0.13 < y2 < 0.
24. The thickness of both the first and second sub-quantum barrier layers is 2.5~5 nm. The quantum well layer is type I. The quantum well layer has a thickness of 2-4 nm, with 0.41 < a < 0.53 and 0.13 < b < 0.
21. The first sub-quantum barrier layer, the quantum well layer, and the second sub-quantum barrier layer form a nip-like junction. The composite transparent conductive layer comprises a wide-bandgap semiconductor superlattice ohmic contact layer, a metal oxide work function adjustment layer, and a wide-bandgap transparent electrode layer, which are stacked sequentially.
2. The deep ultraviolet LED according to claim 1, characterized in that, quantum well In the layer, Al component a is 0.44 and In component b is 0.
15.
3. The deep ultraviolet LED according to claim 1 or 2, characterized in that, The band gap of the wide bandgap semiconductor superlattice structure is larger than that of p-type GaN.
4. The deep ultraviolet LED according to claim 3, characterized in that, The wide-bandgap superlattice ohmic contact layer is Mg-doped. Superlattice structure or Mg doping Superlattice structure, in which, and For the trap layer, and For the layer, a1≠a2, 0.4<a1<0.5, 0.4<a2<0.5, b1≠b2, 0.22<b1<0.29, 0.22<b2<0.29, c1≠c2, 0.35<c1<0.45, 0.65<c2<0.
75.
5. The deep ultraviolet LED according to claim 1 or 2, characterized in that, The metal oxide work function adjustment layer is ITO, FTO, IZO, or Ga-doped ZnO.
6. The deep ultraviolet LED according to claim 1 or 2, characterized in that, The wide-bandgap transparent electrode layer is a graphene layer or a GaO layer, with a thickness of 1 to 4 layers.
7. The deep ultraviolet LED according to claim 4, characterized in that, The wide-bandgap semiconductor superlattice structure has 3 to 10 cycles in its ohmic contact layer. In a single cycle, the thickness of the well layer is 1 nm and the thickness of the barrier layer is 1 nm.
8. The deep ultraviolet LED according to claim 2, 4 or 7, characterized in that, The electron injection layer is an n-type AlGaN layer, and the electron blocking layer is a p-type AlGaN layer.
9. A method for fabricating a high-carrier recombination, high-efficiency deep-ultraviolet LED, characterized in that, Includes the following steps: An epitaxial stack consisting of a buffer layer, an electron injection layer, an MQW active region light-emitting layer, an electron blocking layer, a hole injection layer, and a wide bandgap semiconductor superlattice ohmic contact layer is sequentially grown on the substrate. The epitaxial stack is etched to a certain depth in the electron injection layer to form an n-type platform; A metal oxide work function adjustment layer and a wide bandgap transparent electrode layer are sequentially formed on the wide bandgap semiconductor superlattice ohmic contact layer, and the wide bandgap semiconductor superlattice ohmic contact layer, the metal oxide work function adjustment layer and the wide bandgap transparent electrode layer constitute a composite transparent conductive layer. A p-type electrode is formed on the wide-bandgap transparent electrode layer, and an n-type electrode is formed on the platform; The MQW active region light-emitting layer comprises multiple periodic structures. Each periodic structure consists of a first sub-quantum barrier layer, a quantum well layer, and a second sub-quantum barrier layer stacked sequentially. The first sub-quantum barrier layer has an Al composition that gradually increases. The second sub-quantum barrier layer has a gradually decreasing Al composition. The quantum well layer has the following characteristics: x1 increases from 0.48 to 0.62, x2 decreases from 0.62 to 0.48, 0.13 < y1 < 0.24, and 0.13 < y2 < 0.
24. The thickness of both the first and second sub-quantum barrier layers is 2.5~5 nm. The quantum well layer is type I. The first sub-quantum barrier layer, the quantum well layer, and the second sub-quantum barrier layer form a nip-like junction, with the following parameters: 0.41 < a < 0.53, 0.13 < b < 0.
21. The thickness of the quantum well layer is 2-4 nm.
Citation Information
Patent Citations
Ultraviolet light-emitting diode with p-i-n type multi-quantum well structure
CN113257962A
Near-uv light emitting diode having barrier layer of superlattice structure
KR1020080089044A